Beckwith–Wiedemann syndrome and long QT syndrome due to familial‐balanced translocation t(11;17)(p15.5;q21.3) involving the KCNQ1 gene. (14th November 2012) - Kaltenbach, S; Capri, Y; Rossignol, S; Denjoy, I; Soudée, S; Aboura, A; Baumann, C; Verloes, A
<x xml:space="preserve">Abstract</x> We report a child with Beckwith–Wiedemann syndrome (BWS) as the consequence of an apparently balanced, maternally inherited reciprocal translocation t(11;17)(p15.5;q21.3). His mother and aunt, who inherited the translocation from their father, did not have BWS. At birth, long QT syndrome (LQTS) was diagnosed in this child and, secondarily, among apparently healthy family members carrying the translocation. By FISH analysis, the breakpoint in 11p15.5 interrupts the KCNQ1 gene between exons 2 and 10 and causes a loss of methylation of the IC2 (and thus BWS) on the maternally inherited der(11) chromosome. To explain the presence of LQTS segregating with the t(11;17) translocation in this family, we hypothesize that the translocation that interrupts KCNQ1 allow translation of an abnormal short allele that interferes in a dominant negative way with the normal isoform 1 of KCNQ1 in the heart (where this allele is not subject to parental imprint). This appears to be the first report of BWS with congenital LQTS, which should be considered as a rare but serious complication to be searched systematically in patients with BWS due to 11p15 rearrangements.